Factors Influencing Young Muslim Women's Decisions in Buying Halal Skincare - Halida Bahri; Naufal Bachri; Saharuddin Saharuddin; Sutriani Sutriani; Zulkifli Zulkifli (Faculty of Economics and Business, Universitas Malikussaleh, 2023)
This study aims to examine the influence of lifestyle factor, religiosity, and consumer perceptions on young Muslim women's decisions to buy halal skincare in the Kota Lhokseumawe. This study uses primary data obtained by distributing structured questionnaires to 112 respondents. The sample was selected with a purposive sampling approach. The data analysis method used is multiple linear regression with the help of SPSS Software. The results of the study indicate that lifestyle, level of religiosity, and consumer perception have positive dan significant effect on young Muslim women's decisions in buying halal skincare products in Kota Lhokseumawe. This finding has implications for the development of the concept of purchasing halal products.